Mindfulness Plus Reflection Training: Effects on Executive Function in Early Childhood - Zelazo, Philip David; Forston, Jessica L.; Masten, Ann S.; Carlson, Stephanie M. (Frontiers in Psychology, 2018)
Executive function (EF) skills are essential for academic achievement, and poverty-related stress interferes with their development. This pre-test, post-test, follow-up randomized-control trial assessed the impact of an intervention targeting reflection and stress reduction on children’s EF skills. Preschool children (N = 218) from schools serving low-income families in two U.S. cities were randomly assigned to one of 3 options delivered in 30 small-group sessions over 6 weeks: Mindfulness + Reflection training; Literacy training; or Business as Usual (BAU). Sessions were conducted by local teachers trained in a literacy curriculum or Mindfulness + Reflection intervention, which involved calming activities and games that provided opportunities to practice reflection in the context of goal-directed problem solving. EF improved in all groups, but planned contrasts indicated that the Mindfulness + Reflection group significantly outperformed the BAU group at Follow-up (4 weeks post-test). No differences in EF were observed between the BAU and Literacy training groups. Results suggest that a brief, small-group, school-based intervention teaching mindfulness and reflection did not improve EF skills more than literacy training but is promising compared to BAU for improving EF in low-income preschool children several weeks following the intervention.